Current practices and emerging possibilities for reducing the spread of oomycete pathogens in terrestrial and aquatic production systems in the European Union. (June 2022) - Benavent-Celma, Clara; López-García, Noelia; Ruba, Tahmina; Ściślak, Magdalena E.; Street-Jones, David; van West, Pieter; Woodward, Stephen; Witzell, Johanna
Abstract: Diseases caused by oomycete pathogens are a global threat to forestry, agriculture and aquaculture. Because of their complex life cycles, characterised by dormant resting structures that enable their survival for years under hostile environmental conditions, reducing the spread of oomycetes is a challenging task. In this review, we present an overview of this challenge, starting from the need to understand the natural and anthropogenic dispersal pathways of these pathogens. Focusing on the European Union, we explore current legislation that forms a backbone for biosecurity protocols against the spread of oomycetes through trade and transport. We discuss the options for prevention, containment and long-term management of oomycetes in different production settings, emphasising the importance of prevention as the most cost-efficient strategy to reduce the spread of these pathogens. Finally, we highlight some of the new and emerging technologies and strategies as potential tools in the integrated pest management of animal and plant diseases caused by oomycetes. We emphasise the urgency of actions to halt the global spread of these pathogens.